Intravenous Calcium-/Zinc-Diethylene Triamine Penta-Acetic Acid in Patients With Presumed Gadolinium Deposition Disease: A Preliminary Report on 25 Patients. Issue 6 (June 2018) - Semelka, Richard C.; Ramalho, Miguel; Jay, Michael; Hickey, Lisa; Hickey, Joseph
Abstract : Objectives: The aim of this study was to report the use of intravenous calcium (Ca)-/zinc (Zn)-diethylene triamine penta-acetic acid (DTPA) for the treatment of 25 symptomatic patients diagnosed with gadolinium deposition disease (GDD). Materials and Methods: Written informed consent was obtained. Twenty-five patients (18 women; mean age, 46.8 ± 15.3 years) with a diagnosis of GDD were included. All patients had received at least 1 administration of a gadolinium (Gd)-based contrast agent. Patients received 3 treatment sessions with Ca-/Zn-DTPA, 15 with treatments spaced 1 month apart, and 10 with treatments spaced 1 week apart. In all cases, every treatment consisted of an application of Ca-DTPA and Zn-DTPA separated by 24 hours. Measurements of 24-hour urine Gd content before dosing and on the first and second days of therapy were performed. Symptomatic improvement of patients was determined by use of a 10-point scale of patient symptoms. Serum electrolytes were quantified. Results: Gadolinium content increased in the urine, with an overall mean of 30.3-fold increase in the monthly regimen ( P < 0.001) and 12.9-fold in the weekly regimen ( P < 0.001). Eleven patients experienced transient worsening of at least some of their symptoms, termed a "flare-up" phenomenon, in most of whom symptoms improved or receded. Overall, symptoms improved in 13 patients, unchanged in 10, and worse in 2. Significant clinical improvement was present for headache, brain fog, and bone pain for the monthly regimen and arm pain and leg pain for the weekly regimen. There were no significant changes in major serum electrolytes. Conclusions: Three courses of intravenous Ca-/Zn-DTPA therapy results in significantly increased urine content of Gd after treatment and moderate symptomatic improvement.